The Tales of Beedle the Bard (Hogwarts Library) - Joanne Kathleen Rowling (UK Bloomsbury, 2008)
From J. K. Rowling, a new addition to the bookshelves of every Harry Potter fan: THE TALES OF BEEDLE THE BARDTHE TALES OF BEEDLE THE BARD, a Wizarding classic, first came to Muggle readers' attention in the book known as HARRY POTTER AND THE DEATHLY HALLOWS. Now, thanks to Hermione Granger's new translation from the ancient runes, we present this stunning edition with an introduction, notes, and illustrations by J. K. Rowling, and extensive commentary by Albus Dumbledore.
Keywords: Fantasy; Fiction; Short Stories; Young Adult